Caspases in yeast apoptosis-like death: facts and artefacts - Váchová, Libuse; Palková, Zdena (FEMS yeast research, 2007)
Various findings suggest that programmed cell death (PCD) is induced in yeast as a response to the impact of a deleterious environment and/or an intracellular defect. Moreover, the specifically localized PCD within multicellular colonies seems to be important for the safe degradation of cell subpopulations to simple compounds that can be used as nutrients by healthy survivors occurring in propitious colony areas, being thus important for proper development and survival of the yeast population. In spite of this, the question remains whether yeast dies by real apoptosis, i.e. death involving caspases, or by other kinds of PCD. A large group of mammalian caspases includes those that are responsible for monitoring of the stimulus and initiating the dying process, as well as those involved in the execution of death. Additionally, paracaspases and metacaspases, that share some homology with real caspases, but possibly differ in substrate specificity, have been identified in plants, fungi, Dictyostelium and metazoa. In yeast, one homologue of caspases, metacaspase Mca1p/Yca1p, has been identified so far, although there are several indications of the presence of other caspase-like activities in yeast. In this minireview, we summarize various data on the possible involvement of Mca1p and other caspase-like activities in yeast PCD.
Keywords: Saccharomyces cerevisiae; apoptóza; kaspasy; Caspases; Fungal Proteins; Yeasts; Saccharomyces cerevisiae - proteiny; kvasinky; Saccharomyces cerevisiae Proteins; fungální proteiny; Apoptosis